Guided current-induced skyrmion motion in 1D potential well - Purnama, Indra (2015)
Magnetic skyrmions are particle-like magnetization configurations which can be found in materials with broken inversion symmetry. Their topological nature allows them to circumvent around random pinning sites or impurities as they move within the magnetic layer, which makes them interesting as information carriers in memory devices. However, when the skyrmion is driven by a current, a Magnus force is generated which leads to the skyrmion moving away from the direction of the conduction electron flow. The deflection poses a serious problem to the realization of skyrmion-based devices, as it leads to skyrmion annihilation at the film edges. Here, we show that it is possible to guide the movement of the skyrmion and prevent it from annihilating by surrounding and compressing the skyrmion with strong local potential barriers. The compressed skyrmion receives higher contribution from the spin transfer torque, which results in the significant increase of the skyrmion speed.